2017
DOI: 10.5505/tjtes.2017.27546
|View full text |Cite
|
Sign up to set email alerts
|

The Success of Endotracheal Intubation with a Modified Laryngoscope Using Night Vision Goggles

Abstract: BACKGROUND: Endotracheal intubation (ETI) procedure in the combat area differs from prehospital trauma life support procedures because of the danger of gunfire and the dark environment. We aimed to determine the success, difficulty degree, and duration of ETI procedures with a classical laryngoscope (CL) in a bright room and with a modified laryngoscope (ML) model in a dark room.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…MNVGs are often used by the ground units, whereas BNVG and PNVG are preferred by special forces and military helicopter pilots, as they provide wider temporal vision and depth perception 5 6. Although the tactical use of NVGs has been included in the routine training programme of combatant units, their use has not become widespread in the training and practice of CMS 3 7 8. It has been recommended that the use of NVGs must be included in practical and theoretical training in medical/tactical scenarios in dark conditions 3 4 7 9.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MNVGs are often used by the ground units, whereas BNVG and PNVG are preferred by special forces and military helicopter pilots, as they provide wider temporal vision and depth perception 5 6. Although the tactical use of NVGs has been included in the routine training programme of combatant units, their use has not become widespread in the training and practice of CMS 3 7 8. It has been recommended that the use of NVGs must be included in practical and theoretical training in medical/tactical scenarios in dark conditions 3 4 7 9.…”
Section: Discussionmentioning
confidence: 99%
“…Although the tactical use of NVGs has been included in the routine training programme of combatant units, their use has not become widespread in the training and practice of CMS 3 7 8. It has been recommended that the use of NVGs must be included in practical and theoretical training in medical/tactical scenarios in dark conditions 3 4 7 9. It has also been reported that increasing user experience through practical training increases success rates in interventions using NVGs under dark conditions 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the power analysis, based on previous study findings (completion time 14.46 ± 2.31 s) [19], assuming a completion time of 17.0 s for ETI with an 80% power and a two-sided error margin of 0.05, 18 participants were required. Thus, we planned to include a total of 20 participants who would be randomized to the study groups.…”
Section: Methodsmentioning
confidence: 99%